PENGARUH PENERAPAN STRATEGI KWL (KNOW,WANT,LEARNED) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SD NEGERI CAMBAJAWAYA - Nurfadilah; Syekh Adi Wijaya Latief; Andi Paida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The effect of implementing the KWL (Know, Want, Learned) strategy on the reading comprehension skills of fifth-grade students of Cambajawaya State Elementary School. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor 1 Syekh Adi Wijaya Latief, and Supervisor II Andi Paida. The problem in this study is how to apply the KWL (Know, Want, Learned) strategy to the reading comprehension skills of fifth-grade students of Cambajawaya State Elementary School, Gowa Regency. This study aims to determine the effect of the KWL (Know, Want, Learned) strategy on the reading comprehension skills of fifth-grade students of Cambajawaya State Elementary School. Data were obtained through reading comprehension tests conducted before (pretest) and after (posttest) the implementation of the KWL strategy. The results of data analysis showed that the average pretest score was 36.33 with a standard deviation of 9.726, while the average posttest score increased to 85.83 with a standard deviation of 6.410. This improvement indicates a significant change in students' reading comprehension skills after the implementation of the KWL strategy. After analyzing the data, the author found that students' learning outcomes before the implementation of the KWL strategy were relatively low, as indicated by the average pretest score of 36.33. Furthermore, after the implementation of the KWL strategy, the average posttest score increased to 85.83. This indicates a significant increase in students' reading comprehension skills after the treatment was given. Based on these results, it can be concluded that the use of the KWL strategy has an effect on improving the reading comprehension skills of students at Cambajawaya State Elementary School.